The effect of leptin gene polymorphisms (LEP rs7799039 and LEPR rs1137101) on febrile neutropenia - Ezgi Paslı Uysalol; Metin Uysalol; Istemi Serin; Mustafa Pehlivan; Yasemin Oyaci; Sacide Pehlivan; Zeynep Karakas (Heliyon, 2024)
Background and aim: Leptin is mainly produced in adipose tissue and released into systemic circulation. Leptin and its receptor LEPR activate the Janus kinase/signal transducers and activators of transcription signaling cascade and increase cytokine discharge. In our study, we aimed to examine the role of leptin gene (LEP) rs7799039 and LEPR rs1137101 polymorphisms on the susceptibility for febrile neutropenia (FEN) attacks and their relationship with clinical findings during the course of FEN. Methods: This study included pediatric patients with a diagnosis of malignancy who applied to the pediatric emergency department between December 2019 and June 2022 and healthy controls. The genotypes of the LEP rs7799039 and LEPR rs1137101 genes were statistically compared between patients and healthy controls. In addition, the relationship between the genotype distribution of LEP rs7799039 and LEPR rs1137101 polymorphisms and clinical features during the course of FEN was investigated. Results: In the statistical analysis in terms of LEP rs7799039 and LEPR rs1137101 genotype distributions between the patient and healthy groups, there was no significant difference. Patients with the AA genotype of LEPR rs1137101 polymorphism had significantly more commonly a body mass index (BMI) value of <25, and all the patients with the AG/GG genotype had a BMI value of 25 and above. LEP rs7799039 and LEPR rs1137101 genotype distributions were not statistically significant with other clinical features. Conclusions: It was revealed that leptin gene polymorphisms did not have a significant effect during the course of FEN.